Studi Pengaruh Metode Pengendalian Motor Terhadap Konsumsi Energi Pada Sistem Cooling Tower - Meilani Putri, Andina; Asri, Rishal; Yunesti, Putty (P3M Politeknik Negeri Cilacap, 2025)
Cooling tower fan motors commonly still operate using a direct-on-line (DOL) system with constant speed, which leads to high energy consumption. This study aims to compare the energy consumption between the DOL system and the variable speed drive (VSD), as well as to evaluate their economic feasibility. A quantitative approach is applied through operational data analysis and simulations using MATLAB Simulink. Two operating scenarios are tested: full operation using DOL and using VSD. The simulation results showed that VSD was able to reduce energy consumption by 22.08 without reducing cooling efficiency. The economic evaluation is carried out through a payback period analysis based on investment costs and annual energy savings. These findings demonstrate that VSD is economically viable and can be gradually implemented as an energy efficiency strategy in high-load cooling systems.